2005
DOI: 10.1111/j.1440-1711.2005.01369.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral vaccination of mice with lipid‐encapsulated Mycobacterium bovis BCG: Anatomical sites of bacterial replication and immune activity

Abstract: Summary Lipid microencapsulation of Mycobacterium bovis bacille Calmette-Guérin (BCG) produces an oral delivery vaccine that can establish systemic cell-mediated immune reactivity and protection against aerosol mycobacterial challenge in mice. Here, we describe the lymphatic and mucosal sites of bacterial replication, and location of Mycobacterium -specific IFN-γ -secreting cell populations, following oral vaccination of BALB/c mice. Eight weeks following a single oral dose of lipid-encapsulated BCG, viable BC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…While many novel TB vaccines have been developed [4,5], few have demonstrated protective efficacy that can surpass BCG, which remains the only vaccine approved for human use. Previous research indicates that addition of adjuvant components to the BCG vaccine significantly enhances immune responses to promote host protection against subsequent challenge with virulent MTB [6][7][8][9]. One such reported component is lactoferrin, an iron binding protein found primarily in mucosal secretions and secondary granules of neutrophils [10].…”
Section: Introductionmentioning
confidence: 99%
“…While many novel TB vaccines have been developed [4,5], few have demonstrated protective efficacy that can surpass BCG, which remains the only vaccine approved for human use. Previous research indicates that addition of adjuvant components to the BCG vaccine significantly enhances immune responses to promote host protection against subsequent challenge with virulent MTB [6][7][8][9]. One such reported component is lactoferrin, an iron binding protein found primarily in mucosal secretions and secondary granules of neutrophils [10].…”
Section: Introductionmentioning
confidence: 99%
“…Since BCG is a live-attenuated bacterium, it needs to be protected from degradation in the stomach of an animal if it is to be deployed as an oral vaccine. An edible lipid matrix has been developed that allows BCG bacilli to be maintained in a viable but static state that is suitable as an oral delivery vehicle for the vaccine (Aldwell et al 2005). Studies in a range of animal species have shown that oral vaccination with this lipid-formulated BCG can induce a level of protection against experimental challenge with Tb that is comparable with that induced by injecting the vaccine (Aldwell et al 2003a,b;Buddle et al 2006;Nol et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…One approach may involve targeting the intestinal lymphatic regions, which have been routinely explored and used for site-specific lymphatic delivery of orally administered proteins, drugs, and vaccines (4,83,271). Some alternative Se-delivery approaches have been attempted and shown to ameliorate colitis in an animal model (168).…”
Section: Can Se Supplementation Be Targeted To the Immune System?mentioning
confidence: 99%